Myelodysplastic syndrome in a child with a history of medulloblastoma - Akyüz, Canan; Emir, Suna; Güler, Nilüfer; Türker, Alev; Büyükpamukçu, Münevver (The Turkish Journal of Pediatrics, 1998)
We present a case of myelodysplastic syndrome (MDS) following treatment for medulloblastoma. The tumor was diagnosed at 15 years of age and managed with surgery, craniospinal radiation and a triple-durg regimen [chloroethylnitrosourea (CCNU), vincristine (VCR), procarbazine]. Fifteen months after the completion of therapy, the patient developed MDS with monosomy 5 and monosomy 7 on chromosome analysis of bone marrow cells. Two weeks later, MDS evolved into acute myeloblastic leukemia (AML). Therapy-related MDS or AML may be a complication for patients with past brain tumors. Therefore, they should be carefully followed up by regular physical examinations and complete blood counts.
Keywords: medulloblastoma; myelodysplastic syndrome; second malignancy; monosomy 5; monosomy 7